PENGARUH KOMUNITAS MOTOR LITERASI SEBAGAI GERAKAN SOSIAL TERHADAP PERKEMBANGAN CIVIC LITERACY DI KOTA SERANG - Alamsyah Basri; Muhammad Asmawi; Ahmad Asqolani (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2019)
This study aims to determine how much influence the Komunitas Motor Literasi as a Social Movement on the Development of Civic Literacy in Serang City. This study uses a quantitative approach, namely research whose data is in the form of numbers. The method used in this research is descriptive quantitative research method that is by finding information about the existing symptoms, clearly defined the objectives to be achieved, planning the approach, collecting data as material for making reports. The main data collection technique uses questionnaire techniques with questionnaire instruments and is supported by documentation observation and study. The subjects of this study were the people in Serang City who visited the Komunitas Motor Literasi which consisted of 84 respondents.The results of the data processing, the Komunitas Motor Literasi as a social movement has a strong influence on the development of civic literacy in Serang City, with a total score of 5097 or if presented in the amount of 80.90% and equal to 0.688 of indicators of relevance, the latest collection of books and new social movements . Then based on the results of the calculation of the data, the results were 0.473 (r-square) which showed that the Komunitas Motor Literasi as a social movement contributed 47.3% to the development of civic literacy in Serang City while the remaining 52.7% was influenced by other variables that could not be explained in this research.